Analisis Modul Proyek Penguatan Profil Pelajar Pancasila Kelas IV di UPTD SDN Kraton 1 Bangkalan - Arining, Ahadini Dwi; Fajrin, Nilamsari Damayanti (Yayasan Arrahman Nahdlatul Wathan, 2024)
The purpose of this research is to determine the suitability of developing project modules at the UPTD SDN Kraton 1 Bangkalan school with guidelines for developing profile projects. Based on Minister of Education and Culture Decree No.262/M/2022, the theme provisions applied at the elementary school level are 2 to 2. 3 different themes in 1 school year. The approach taken in this research is descriptive quantitative research. The data collection used was a questionnaire sheet. The results obtained in this research show that: The school has fulfilled 2 different themes in 1 academic year with module components that are in accordance with the project development guidelines for strengthening the Pancasila student profile. The customized project module components include mapping of themes, dimensions, elements and sub-elements, activity flow, and assessment design based on phase development for class IV, namely phase B. The completeness and suitability of the module obtained 100% results. The results of the researcher's data analysis were agreed upon by 2 observers. From the calculation of the agreement coefficient, the result was 1. A value of 1 > 0.75, if categorized using recapitulation of observation calculations, received a very good category.